Comparison of the Effect of Massage with Coconut Oil and Sunflower Oil on the Growth of Premature Infants - P Aziznejadroshan (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Prematurity and low birth weight are one of the major health problems and the most common causes of infant mortality. Infant massage is potentially beneficial for physiological and psychological health. The present study was conducted to compare the effect of massage with coconut oil and sunflower oil on the growth of premature infants. METHODS: This clinical trial was performed on 100 premature infants admitted to the neonatal intensive care unit of Amirkola Children's Hospital in 2018 in four groups of 25 infants. Infants of the intervention groups with one cc of sunflower oil and coconut oil and the oil-free massage group were massaged for 15 minutes three times a day for seven days with the help of a research assistant, and the control group received only routine care. The weight, height, and head circumference of infants were collected using a personal profile questionnaire and compared in four groups at the beginning and end of the intervention. FINDINGS: Comparison of mean weight and head circumference changes at the end of the first week between coconut oil massage group (0.134±0.334 cm, 6.81±3.04 g), sunflower oil massage group (0.239±1.172 cm, 6.35±2.69 g), oil-free massage group (1.061±1.534 cm, 2.95±2.65), and control group (0.663±1.174 cm, 3.52±4.38 g) showed significant difference (p<0.05). Comparison of mean height changes in different groups (0.413±0.739, 0.448±0.747, 0.458±0.693, 0.429±0.611 cm, respectively) did not show any significant difference. CONCLUSION: The results of the study showed that oil massage is recommended as it increases the rate of changes in weight gain and head circumference in premature infants.